PENGEMBANGAN MEDIA PEMBELAJARAN DI MI DAN SD - Nawali, Jazilatun; Ivtari Savika, Helda; Kharismatul Mufidah , Intan; Susilawati, Samsul (CAHAYA: Journal of Research on Science Education, 2024)
The development of learning media has become the main focus in the contemporary educational era. Learning media development models, such as the Borg and Gall Model, have become an important basis for developers in designing effective and quality learning media. The Borg and Gall model is a systematic and comprehensive approach used to develop effective and relevant learning media in Madrasah Ibtidaiyah (MI) or Elementary Schools (SD). This approach emphasizes research and development (R&D) to produce educational products that are practical and can be directly applied in the classroom. The process involves several stages starting from problem identification, prototype development, field trials, to product evaluation and revision. This article uses a literature study research method by presenting an in-depth analysis of the Borg and Gall model in developing learning media, which includes basic concepts, characteristics, steps, as well as the strengths and weaknesses of this model in developing learning media. With a deep understanding of the characteristics and principles contained in this model, educational practitioners can improve the quality of learning through the application of more effective learning media.